Thermo-photo synergic effect on methanol steam reforming over mesoporous Cu/TiO2–CeO2 catalysts. (3rd August 2021) - Liu, Xianglei; Bao, Chuang; Zhu, Zhonghui; Zheng, Hangbin; Song, Chao; Xu, Qiao
Abstract: Methanol steam reforming (MSR) is considered as an effective method for hydrogen storage and generating high-quality hydrogen for fuel cells. In this work, mesoporous Cu/TiO2 –CeO2 catalysts are proposed to achieve efficient MSR based on synergetic effects of thermal and photon energies. Optimal Ti/Ce molar ratio is found to be 2:1, for which excellent methanol conversion of 100% and extremely low CO selectivity of 2.2% are achieved for thermal catalysis. Further applying UV light (280–400 nm) irradiation while keeping the same temperature, the hydrogen production rate is enhanced to be 78.8 mmol/h/g from 58.6 mmol/h/g. The underlying mechanism is attributed to photogenerated electron hole pairs promoting the REDOX reaction of intermediate product methyl formate based on in situ diffuse reflectance infrared fourier transform spectra (DRIFTS). This work provides a new method to enhance methanol steam reforming performance via thermo-photo synergic effects, and paves a way for the development of direct solar driven MSR techniques. Highlights: High-performance Cu/2TiO2 –CeO2 catalyst with superb product selectivity is proposed. Hydrogen production rate is enhanced significantly under UV light irradiation. Thermo-photo synergic effects promote reactions of intermediate methyl formate.